Microglial CD2AP deficiency exerts protection in an Alzheimer’s disease model of amyloidosis - Lingliang Zhang; Lingling Huang; Yuhang Zhou; Jian Meng; Liang Zhang; Yunqiang Zhou; Naizhen Zheng; Tiantian Guo; Shanshan Zhao; Zijie Wang; Yuanhui Huo; Yingjun Zhao; et al. (Molecular Neurodegeneration)
Abstract Background The CD2-associated protein (CD2AP) was initially identified in peripheral immune cells and regulates cytoskeleton and protein trafficking. Single nucleotide polymorphisms (SNPs) in the CD2AP gene have been associated with Alzheimer’s disease (AD). However, the functional role of CD2AP, especially its role in microglia during AD onset, remains elusive. Methods CD2AP protein levels in cultured primary cells and in 5xFAD mice was studied. Microglial CD2AP-deficient mice were crossed with 5xFAD mice and the offspring were subjected to neuropathological assessment, behavioral tests, electrophysiology, RNA-seq, Golgi staining, and biochemistry analysis. Primary microglia were also isolated for assessing their uptake and morphology changes. Results We find that CD2AP is abundantly expressed in microglia and its levels are elevated in the brain of AD patients and the 5xFAD model mice at pathological stages. We demonstrate that CD2AP haploinsufficiency in microglia significantly attenuates cognitive and synaptic deficits, weakens the response of microglia to Aβ and the formation of disease-associated microglia (DAM), and alleviates synapse loss in 5xFAD mice. We show that CD2AP-deficient microglia exhibit compromised uptake ability. In addition, we find that CD2AP expression is positively correlated with the expression of the complement C1q that is important for synapse phagocytosis and the formation of DAM in response to Aβ deposition. Moreover, we reveal that CD2AP interacts with colony stimulating factor 1 receptor (CSF1R) and regulates CSF1R cell surface levels, which may further affect C1q expression. Conclusions Our results demonstrate that CD2AP regulates microgliosis and identify a protective function of microglial CD2AP deficiency against Aβ deposition, suggesting the importance of detailed investigation of AD-associated genes in different brain cells for thoroughly understanding their exact contribution to AD.